Net primary production in the Gulf Stream sustained by quasi‐geostrophic vertical exchanges. Issue 2 (22nd January 2015) - Pascual, Ananda; Ruiz, Simón; Buongiorno Nardelli, Bruno; Guinehut, Stéphanie; Iudicone, Daniele; Tintoré, Joaquín
Abstract: We analyze 12 years of mesoscale vertical motion derived from an observation‐based product in the top 1000 m of the North West Atlantic Ocean. Vertical velocities (O(10 m d −1 )) associated with Gulf Stream instabilities consist of alternating cells of upwelling and downwelling. Here we show that the magnitude of the vertical motions decays exponentially southward with an e ‐folding length scale that is informative on the dynamics of the system. We further investigate the impact of the vertical supply of nutrients about phytoplankton growth with a conceptual model incorporating the mean effect of nutrient distribution, quasi‐geostrophic dynamics, and Ekman suction/pumping. Results confirm that the mean effect of mesoscale vertical velocity variability alone can sustain observed levels of net primary production in the immediate vicinity of the Gulf Stream, while other mechanisms, including horizontal advection and submesoscale dynamics, need to be considered when moving toward the subtropical gyre. Key Points: New estimation of vertical velocity derived from an observational‐based approach QG‐vertical velocities can sustain net primary production in the Gulf Stream The same methodology can be applied to other regions of the Global Ocean